Depictions of Masculinity, Paternity / Maternity, and Upbringing in the Anarchist Newspaper Vida Nueva (Chile, 1934-1942); [Masculinidad, Paternidad / Maternidad y Crianza en el Periódico Anarquista Vida Nueva (Chile, 1934-1942)] - Godoy-Sepulveda, E (Universidad Pablo de Olavide, 2023)
In this investigation, preliminary antecedents are provided for reflecting on the discursive construction and projections of anarchists in the Chilean south with respect to their conception of masculinity, relating it also to their views on paternity, maternity, and upbringing. The study reviews and analyzes the content of the anarcho-syndicalist newspaper Vida Nueva, published in the southern city of Osorno between 1934 and 1942. It is argued that the anarchists of southern Chile, though they sought to question and stress gender roles by discussing the detrimental situation of women in local society, failed to break with the socio-cultural order and, on the contrary, reproduced a conservative logic through their conceptions of paternity, maternity, and upbrining. In this way, they reinforced the role of “father-man-provider” and attributed to women (unchangeable) mandates from a biological and traditional/conservative perspective. © 2023, Universidad Pablo de Olavide. All rights reserved.